Controlling Structural Symmetry of a Hybrid Nanostructure and its Effect on Efficient Photocatalytic Hydrogen Evolution. (12th December 2013) - Zhao, Qian; Ji, Muwei; Qian, Hongmei; Dai, Baosong; Weng, Lin; Gui, Jing; Zhang, Jiatao; Ouyang, Min; Zhu, Hesun
<x xml:space="preserve">Abstract</x> The existence of lattice strain between two different materials can be used to control the fine structural configuration in a hybrid colloidal nanostructure. Enabled by such, the relative position change of Au and CdX in Au‐CdX from a symmetric to an asymmetric configuration is demonstrated, which can further lead to fine tuning of plasmon‐exciton coupling and different hydrogen photocatalytic performance. These results provide new insight into plasmon enhanced photocatalytic mechanisms and provide potential catalysts for photoreduction reactions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>